Optimized design for data processing and power consumption for wireless sensor node - Sabri Salim, Muhammed (International Journal of Engineering and Technology, 2019)
The primary processing of data collected in the sensor node is a major aspect of the performance of wireless sensor networks. This paper provides an experimental description of a smart algorithm in which the sensitivity node operates. The specification is based on measuring the current that is discharged from the power source in data transmissions. The measurements allow for the definition of an analytical model for the number of data packets to be sent from the terminal sensor node, a function of sensor operation and the level of change of sensor data. Conventional sensor nodes are not effective in terms of productivity, flexibility, energy consumption and work interference. The sensor node is programmed according to the conventional method, which sends the data every minute, and then reprogrammed according to the intelligent algorithm in which the transmitter unit is activated when there is a difference between the averages of ten readings in one minute with the previous average reading. Temperature and humidity were measured over a 12-hour period. The conventional sensor node needed to send 60 packets of data within an hour, which could be repeated data. The use of the smart node algorithm improved current consumption by 93% compared to the commercial node. The integration of the wireless sensor node with the smart algorithm has several advantages, such as the number of packet data sent is lower and of high accuracy, the total power consumed for the node is lower. In addition to the possibility of increasing the number of sensor nodes in the wireless sensor network.Â Â